Training Online Physical Educators: A Phenomenological Case Study. (16th July 2017) - Goad, Tyler; Jones, Emily
Abstract : Online physical education (OLPE) presents a unique set of challenges in translating traditional physical education to a digital space, all while meeting the same benchmarks, curriculum, and assessment standards of traditional courses. Currently, limited research exists investigating how physical educators are formally trained to deliver content online. Therefore, the purpose of this study was to describe the experiences and perceptions of students and instructor of a graduate-level OLPE teacher education (OLPETE) methods course. A phenomenographic research design was employed to examine the social phenomenon of one OLPETE methods course at a midwest midmajor college. Participants in this study were an instructor of OLPETE methods course and former students who had completed the course. Data for the case study were collected through semistructured interviews and inductive content analysis was employed to analyze the qualitative data. Results revealed four categories describing the lived experiences of those involved: (1) Modeling Online Instructional Practices, (2) Instructor and Student Interactions, (3) Transitioning Pedagogical and Content Knowledge Online, and (4) Navigating Instructional Tools and Technology.